Strategi Promosi Untuk Meningkatkan Animo Orang Tua Menitipkan Anaknya di TPA Rumah Bermain Al-Farizi Pangkalpinang - Rafelina, Dila (ICEJ : Islamic Childhood Education Journal, 2022)
In modern times now parents are busy working, usually only fathers who work now mother are already working a lot to help the family economy. With that a lot of parents who leave their children with the family or day care (TPA). But there are still many parents who do not know very well what TPA is and what activites are, therefore to introduce TPA to the general public, the institution should have promoted.